On moment indeterminacy of the Benini income distribution - Christian Kleiber (University of Basel, Center of Business and Economics (WWZ), 2013)
The Benini distribution is a lognormal-like distribution generalizing the Pareto distribution. Like the Pareto and the lognormal distributions it was originally proposed for modeling economic size distributions, notably the size distribution of personal income. This paper explores a probabilistic property of the Benini distribution, showing that it is not determined by the sequence of its moments although all the moments are finite. It also provides explicit examples of distributions possessing the same set of moments. Related distributions are briefly explored.
Keywords: C46; C02; 330; Benini distribution; characterization of distributions; income distribution; moment problem; statistical distributions; Stieltjes class; Einkommensverteilung; Statistische Verteilung; Statistische Methode; Konzentrationsmaß